Only children or siblings: Who has higher physical activity and healthier weight? - Sigmund, Erik; Sigmundová, Dagmar (Acta Gymnica, 2021)
Background: The influence of parents on physical activity (PA) and body weight of their children is confirmed by scientific studies. However, it is not known whether only children or those with siblings have a higher level of PA and healthier body weight. Objective: The aims of this study are (i) to assess whether there are any differences in the achievement of the daily step count (SC) recommendation and in the prevalence of overweight/obesity between only children and children from families with multiple children, and (ii) to investigate whether the achievement of the SC recommendation by children/parents and parental overweight/obesity is associated with childhood obesity. Methods: The analysis included 566 families (10.6%/89.4% with single child/two or more children) with complete data on weight status and PA monitored with a Yamax pedometer during regular school/work between 2013-2019. The daily SC recommendation amounted to ≥ 13,000/11,000 SC for 5-12-year-old sons/daughters and ≥ 10,000 SC for 12-16-year-old adolescents and adults. The chi-square test was used to compare the achievement of the daily SC recommendation and the prevalence of overweight/obesity. Binary logistic regression analyses were used to investigate whether the achievement of the daily SC recommendation by children/parents and parental overweight/obesity were associated with obesity in their offspring. Results: A significantly higher proportion of children with siblings achieved the recommended daily SC (51.8% vs. 31.7%, p = .003) and showed a lower prevalence of overweight (16.2% vs. 20.0%, p = .041) and obesity (7.1% vs. 20.0%, p < .001) compared with only children. The achievement of the daily SC recommendation in children significantly (p < .05) decreased the odds ratio of obesity (odds ratios 0.22-0.34, 95% confidence intervals 0.07-0.85). Conclusions: Children from families with siblings had higher physical activity and healthier body weight than those from single-child families. However, reaching the recommended daily SC reduces the likelihood of childhood obesity, regardless of the presence of a sibling in the family.
Keywords: Research; obezita dětí a dospívajících; výzkum; sourozenci; Obesity; Family; Parents; Child; lidé; rodina; obezita; dítě; Siblings; rodiče; Pediatric Obesity; Humans